Case Report: Notoedric Mange and Aelurostrongylidosis in Two Domestic Cats From Rural Environment in Romania - Györke, Adriana; Dumitrache, Mirabela Oana; Ursache, Aurora Livia; D'Amico, Gianluca; Mircean, Viorica (Frontiers in Veterinary Science, 2022)
This article describes two cases of notoedric mange concurrent with aelurostrongylidosis in two domestic-owned cats from a rural environment in Romania. Two European shorthair cats originating from the same litter were referred to our clinic, at 2 months apart, with a history of skin lesions, pruritus, weight loss, and respiratory signs. Cats lived mainly outdoor together with the queen and a third littermate. The latter two expressed the same clinical signs and had died before the presentation of the first cat. None of the four cats was vaccinated, dewormed, or treated for external parasites. Coat brushing, skin scrapings, skin cytology, earwax direct microscopic examination, and coproparasitological techniques (flotation and Baermann methods) were used as laboratory procedures. A blood sample was also collected for hematology, blood biochemistry, and feline immunodeficiency virus/feline leukemia virus (FIV/FeLV) test. Notoedres cati mites in high numbers were identified by all complementary tests, alongside fleas and Aelurostrongylus abstrusus first-stage larvae. The blood analysis revealed neutrophilia, and the FIV/FeLV fast test was negative. The cats were successfully treated off-label with selamectin spot-on formulation (Stronghold®, Zoetis) three times at 1- or 4-week intervals. Furthermore, they were treated with amoxicillin trihydrate/clavulanic acid, housed indoor, and fed with a commercial diet. Before presentation to the clinic, the female cat was unsuccessfully treated with a combination of fipronil, S-methoprene, eprinomectin, and praziquantel. During this period, the female cat remained outdoor and fed with home wastes. The cats become negative for A. abstrusus L1 larvae after 2–4 months of treatment. The owners developed pruritic skin lesions 1 month after introducing the first cat in the house. In conclusion, notoedric mange and aelurostrongylidosis can be treated successfully with selamectin as a spot-on formulation and the treatment must be continued until no parasite will be detected through specific techniques. The success of treatment depends on improving the quality of animal life (nutrition and hygiene) and treatment of secondary complications.